2019
DOI: 10.1093/jac/dkz514
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans enhances meropenem tolerance of Pseudomonas aeruginosa in a dual-species biofilm

Abstract: Background Pseudomonas aeruginosa is an opportunistic bacterium that infects the airways of cystic fibrosis patients, surfaces of surgical and burn wounds, and indwelling medical devices. Patients are prone to secondary fungal infections, with Candida albicans being commonly co-isolated with P. aeruginosa. Both P. aeruginosa and C. albicans are able to form extensive biofilms on the surfaces of mucosa and medical devices. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…These infections are commonly associated with biofilm formation, especially in patients with dentures, voice protheses and xerostomia (reduced or absent saliva flow). Biofilm formation makes these infections difficult to treat because they are generally polymicrobial in nature, and the production of extracellular matrix increases the resistance to antimicrobial therapy [ 5 , 6 , 84 ]. Oral candidiasis is prevalent in immunosuppressed individuals such as HIV patients, mouth and throat cancer patients, and patients taking oral steroids making them highly susceptible to infection.…”
Section: Niche-specific Immune Sensing Of C Albicansmentioning
confidence: 99%
“…These infections are commonly associated with biofilm formation, especially in patients with dentures, voice protheses and xerostomia (reduced or absent saliva flow). Biofilm formation makes these infections difficult to treat because they are generally polymicrobial in nature, and the production of extracellular matrix increases the resistance to antimicrobial therapy [ 5 , 6 , 84 ]. Oral candidiasis is prevalent in immunosuppressed individuals such as HIV patients, mouth and throat cancer patients, and patients taking oral steroids making them highly susceptible to infection.…”
Section: Niche-specific Immune Sensing Of C Albicansmentioning
confidence: 99%
“…However, it appears that these microorganisms are not powerless in front of P. aeruginosa and can even take advantage of this interaction within mixed-species biofilm. Antimicrobial resistance and virulence of C. albicans and P. aeruginosa are thus enhanced during their interaction, particularly through an increased production of phenazines by P. aeruginosa and ethanol by C. albicans ( Fourie et al, 2016 ; O’Brien and Fothergill, 2017 ; Fourie and Pohl, 2019 ; Alam et al, 2020 ; Bandara et al, 2020 ; Hùlková et al, 2020 ; Ibberson and Whiteley, 2020 ). In the same way, P. aeruginosa alginate can protect B. cenocepacia from the host immune system ( O’Brien and Fothergill, 2017 ).…”
Section: P Aeruginosa and S Aureus Are mentioning
confidence: 99%
“…albicans enhanced P. aeruginosa ECM production, consisting of proteins, polysaccharides, and nucleic acids, through increased expression of the alginate genes AlgU and mucA [171]. Alam et al (2019) showed C. albicans can enhance meropenem tolerance of P. aeruginosa in a dual-species biofilm [172]. They concluded that fungal mannan and glucan secreted into the ECM of a dual species biofilm of P. aeruginosa and C. albicans increases P. aeruginosa tolerance to meropenem.…”
Section: Impact On Antimicrobial Resistancementioning
confidence: 99%